Analisis Sistem Akuntansi Persediaan Bahan Baku Dalam Upaya Meningkatkan Pengendalian Intern - Wahyuni, Iis; Wulan, Ratna Sekar (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Raw material inventory control is a problem issue faced by manufacturing companies where the balance of raw material inventory based on company records is not relevant to the balance of raw material inventory in the warehouse. The company must control the raw material inventory balance effectively. Control of raw material inventory systems can be measured when the recorded data are of equal amount when compared to the physical materials in the warehouse. This study is aimed at investigating how companies control its system of accounting for raw material inventories as an effort to improve internal control. The method applied in this study is qualitative descriptive analysis. The result of the study show that when a company uses a system of accounting for raw material inventories starting from the procedure for receipt of raw material inventories from suppliers to the procedure of raw material inventory in the warehouse. The company can get the order of raw materials that are ordered from the supplier, facilitating the fulfillment of raw materials needed in the production division, minimizing the loss of raw materials in warehouses, increasing the relevance of stock data in systems with stock in warehouses. Still, there are violations to the procedures found, most specifically in the procedure for requesting goods in the warehouse and returning warehouse goods. These violations are due to the flexibility of the standard procedures and warehouse access that is found rather loose to the production division, so as to cause the difference in stock between the stocks of raw material in the warehouse with the stock of raw materials in the system. We can conclude that the increasing internal control of raw material inventories will result in the more effective and efficient costs incurred by the company because it minimizes the risk of fraud and negligence of work.